Dimensions of epistemological beliefs, learning goal orientation, as predictors of deep knowledge acquisition approach among pre-service teachers in Nigeria - Jikamshi, Mahmud Haruna; Abdullah, Maria Chong; Roslan, Samsilah; Ismail, Habsah (Mediterranean Center of Social and Educational Research, 2016)
This study aims to identify the relationship between three dimensions of epistemological beliefs (Simple knowledge, Certainty of knowledge, Quick learning), and learning goal orientation, in predicting deep knowledge acquisition approach among pre-service teachers. We conducted a quantitative correlational study with 418 pre-service teachers from colleges of education in Northern Nigeria. In conducting Pearson correlation and regression analyses, we found there is a significant relationship between all the dimensions of epistemological beliefs, learning goal orientation, and deep knowledge acquisition. More specifically, there is significant negative relationship between simple knowledge, quick learning, and deep knowledge acquisition. However, there is significant positive relationship between certainty of knowledge, learning goal orientation, and deep knowledge acquisition approach. The regression analysis indicates that simple knowledge (SK), certainty of knowledge (CK), and learning goal orientation significantly predict deep knowledge acquisition approach (DKA). However, Quick Learning (QL) did not significantly predict deep knowledge acquisition approach. The present study’s implication is that, it provides insight into one causal mechanism whereby the dimensions of epistemological beliefs, and learning goal orientation impact on pre-service teachers deep knowledge acquisition approaches in typical college settings.